Violation of Human Rights and Enforced Disappearance in Bosnia and Herzegovina (Frontiers in Law, 2023)
Every armed conflict outcome in a violation of fundamental human rights and freedoms. In areas where war conflicts are taking place, certain forms of crimes that are most often committed against civilians and other categories protected by international (humanitarian) law occur as an inevitable consequence. Thus, in the territory of Bosnia and Herzegovina in the war that took place in the period 1992-1995. committed numerous war crimes, and crimes against the peace and security of mankind. These crimes were committed against civilians and protected categories of the population, primarily prisoners of war. The issue of protection of human rights in Bosnia and Herzegovina is inevitably connected with the consideration of the consequences resulting from the armed aggression carried out at the end of the twentieth century. One form of crime that is particularly specific to Bosnia and Herzegovina is the crime of enforced disappearance. Enforced disappearances in Bosnia and Herzegovina are most often associated with the out-of-court detention of persons whose fate becomes unknown upon expulsion from their homes or stays in camps and other places of detention. This form of crime is especially significant because its consequences still last, even though 25 to 30 years have passed since its commission. Namely, the total number of registered forcibly missing persons in Bosnia and Herzegovina is 34,965. About 8,000 more people are wanted. Many families have not yet exercised their basic humanitarian right to know the truth about the fate of their family members. The bodies or remains of forcibly missing persons are most often found in unmarked individual or mass graves of a hidden locality. There are a numerous of forcibly missing persons who are still being searched for, and this is precisely the reason why studying the enforced disappearances of persons and considering the consequences of this committed crime is of special social interest. It is especially important to provide legal protection to families whose members were forcibly disappeared during the war and whose bodies or remains have not been found to date. The humane character of this issue must not be overlooked. It is important to find new possibilities in the search for forcibly missing persons, bearing in mind the fact that the passage of time and the biological processes that take place make it difficult to perform this task. Particular attention should be paid to the fact that witnesses or perpetrators of crimes who can provide adequate information end their lives. The truth about hidden bodies thus remains inaccessible. International bilateral agreements involving stakeholders represent one of the new possibilities in resolving issues related to enforced disappearances.